Peningkatan Kemampuan Bahasa Inggris Siswa Kelas III SMA Islam Terpadu Al-Kamal NW dengan Metode Audio-Visual - Sutarman Sutarman; Zainudin Abdussamad; Abdul Muhid; Lela Rahmawati; Wahyu Kamil Syarifaturrahman (LPPM Universitas Bumigora, 2021)
This service activity aims at training the English ability of the third grade students of SMA Islam Terpadu Al-Kamal NW in Narmada. This service is to solve the lack of human sources in English teachers in this school in which the headmaster plans to encourage students’ ability in English speaking. It is conducted for three months started from March to May in 2021. To implement the service, the team makes some stages consisting of planning, coordination, preparation, training, and evaluation. In training, the audio-visual method is used to increase the students’ ability in mastering English. The results shows that the average score of all students are 74 for pronunciation, 73 for fluency and 72.94 for grammar. The average score indicate that their ability in English mastery is quite good and need to be developed for further. Thus, team expects that this service run continuously and get supports from related stakeholders.